Mechanistic Insight into PPARγ and Tregs in Atherosclerotic Immune Inflammation - Zhao Gao; Zhao Gao; Xinrui Xu; Yang Li; Kehan Sun; Manfang Yang; Qingyue Zhang; Shuqi Wang; Yiyi Lin; Lixia Lou; Aiming Wu; Weijing Liu; et al. (Frontiers Media S.A., 2021)
Atherosclerosis (AS) is the main pathological cause of acute cardiovascular and cerebrovascular diseases, such as acute myocardial infarction and cerebral apoplexy. As an immune-mediated inflammatory disease, the pathogenesis of AS involves endothelial cell dysfunction, lipid accumulation, foam cell formation, vascular smooth muscle cell (VSMC) migration, and inflammatory factor infiltration. The nuclear receptor peroxisome proliferator-activated receptor gamma (PPARγ) plays an important role in lipid metabolism, inflammation, and apoptosis by antagonizing the Wnt/β-catenin pathway and regulating cholesterol efflux and inflammatory factors. Importantly, PPARγ-dependant fatty acid uptake is critical for metabolic programming. Activated PPARγ can exert an anti-atherosclerotic effect by inhibiting the expression of various inflammatory factors, improving endothelial cell function, and restraining the proliferation and migration of VSMCs. Regulatory T cells (Tregs) are the only subset of T lymphocytes that have a completely negative regulatory effect on the autoimmune response. They play a critical role in suppressing excessive immune responses and inflammatory reactions and widely affect AS-associated foam cell formation, plaque rupture, and other processes. Recent studies have shown that PPARγ activation promotes the recruitment of Tregs to reduce inflammation, thereby exerting its anti-atherosclerotic effect. In this review, we provide an overview of the anti-AS roles of PPARγ and Tregs by discussing their pathological mechanisms from the perspective of AS and immune-mediated inflammation, with a focus on basic research and clinical trials of their efficacies alone or in combination in inhibiting atherosclerotic inflammation. Additionally, we explore new ideas for AS treatment and plaque stabilization and establish a foundation for the development of natural PPARγ agonists with Treg recruitment capability.